The Role of Learning Motivation in Mediating the Relationship Between the Perception of the Teaching Profession and Self-Efficacy on the Interest in Becoming an Economics Teacher - Rosalina, Eneng Seli; Sojanah, Janah; Mulyadi, Hari (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aimed to determine the effect of perceptions of the teaching profession and self-efficacy on the interest in becoming an economics teacher, with learning motivation as a mediating variable. The research employed a quantitative approach and was conducted on 55 students of the Economics Education Study Program at Langlangbuana University. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method through the SmartPLS 4.1.1.2 application. The results showed that perceptions of the teaching profession had a significant effect on learning motivation but did not have a significant effect on the interest in becoming a teacher. Likewise, self-efficacy had a significant effect on learning motivation but did not significantly affect the interest in becoming a teacher. Learning motivation had a significant effect on the interest in becoming a teacher. Moreover, learning motivation significantly mediated the relationship between perceptions of the teaching profession and the interest in becoming a teacher, as well as between self-efficacy and the interest in becoming a teacher. These findings confirmed that learning motivation was a key factor in fostering students’ interest in becoming economics teachers. Therefore, it could be concluded that hypotheses H2 and H4 were rejected, while H1, H3, H5, H6, and H7 were accepted in this study. This research contributed substantially to the development of interest in becoming an economics teacher through a deeper understanding of the roles of perceptions of the teaching profession, self-efficacy, and learning motivation as psychological factors that could be strengthened to cultivate students’ commitment and enthusiasm toward the teaching profession in the field of economics.